2005
DOI: 10.1002/fld.955
|View full text |Cite
|
Sign up to set email alerts
|

The advantages of using high-order finite differences schemes in laminar-turbulent transition studies

Abstract: SUMMARYThis paper presents various ÿnite di erence schemes and compare their ability to simulate instability waves in a given ow ÿeld. The governing equations for two-dimensional, incompressible ows were solved in vorticity-velocity formulation. Four di erent space discretization schemes were tested, namely, a second-order central di erences, a fourth-order central di erences, a fourth-order compact scheme and a sixth-order compact scheme. A classic fourth-order Runge-Kutta scheme was used in time. The inuence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
16

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 16 publications
(18 reference statements)
1
16
0
16
Order By: Relevance
“…Adam [3] and Hirsh [4] discussed some advantages of the fourth-order compact methods compared to traditional methods. Souza et al in [5] demonstrated that the sixth-order compact scheme has good agreement with linear stability theory.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Adam [3] and Hirsh [4] discussed some advantages of the fourth-order compact methods compared to traditional methods. Souza et al in [5] demonstrated that the sixth-order compact scheme has good agreement with linear stability theory.…”
Section: Introductionmentioning
confidence: 87%
“…the derivative, is included implicitly in the equation which approximates the derivative. Several papers have been published showing the advantages of this class of methods [2,5,26].…”
Section: Compact Finite Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the normal direction the same idea is adopted in the buffer domain regions. The spatial derivatives are calculated using high order compact finite difference schemes given by Souza et al (2005). The vPoisson is solved using a Full Approximation Scheme (FAS) multigrid with a V-cycle working with 4 grids (Stuben and Trottenberg, 1981).…”
Section: Formulation and Numerical Methodsmentioning
confidence: 99%
“…The equations presented above are discretized by high-order finite-difference schemes [17,13,18,19] and spectral approximations for the spatial derivatives. A fourth-order four-step Runge-Kutta method is used for the temporal integration.…”
Section: Methodsmentioning
confidence: 99%